Two Cases of Sarcoidosis in One Family with Review (Journal of Medicine, 2008)
Sarcoidosis is a multisystemic disease that has an immunological basis. We report a family in which two members have been affected with sarcoidosis. The radiological findings of all cases were presented, together with histopathological diagnosis. The particular interest in this report is the fact that two family members we present here are blood relatives. DOI = 10.3329/jom.v8i2.1414 J MEDICINE 2007; 8 : 76-80